Choline Supplementation With a Structured Lipid in Children With Cystic Fibrosis: A Randomized Placebo-Controlled Trial. Issue 4 (April 2016) - Schall, Joan I.; Mascarenhas, Maria R.; Maqbool, Asim; Dougherty, Kelly A.; Elci, Okan; Wang, Dah-Jyuu; Altes, Talissa A.; Hommel, Kevin A.; Shaw, Walter; Moore, Jeff; Stallings, Virginia A.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: Choline depletion is seen in cystic fibrosis (CF) and pancreatic insufficiency in spite of enzyme treatment and may result in liver, fatty acid, and muscle abnormalities. This study evaluated the efficacy and safety of an easily absorbed choline-rich structured lipid (LYM-X-SORB™ [LXS]) to improve choline status. Methods: Children with CF and pancreatic insufficiency were randomized to LXS or placebo in a 12-month double blind trial. Dietary choline intake, plasma cholines, plasma and fecal phospholipids, coefficient of fat absorption, pulmonary function, growth status, body composition, and safety measures were assessed. Magnetic resonance spectroscopy for calf muscle choline and liver fat were assessed in a subgroup and compared with a healthy comparison group matched for age, sex, and body size. Results: A total of 110 subjects were enrolled (age 10.4 ± 3.0 years). Baseline dietary choline, 88% recommended, increased 3-fold in the LXS group. Plasma choline, betaine, and dimethylglycine increased in the LXS but not placebo ( P  = 0.007). Plasma lysophosphatidylcholine and phosphatidylcholine increased, and fecal phosphatidylcholine/phosphatidylethanolamine ratio decreased ( P  ≤   0.05) in LXS only, accompanied by a 6% coefficient of fat absorption increase ( P  = 0.001). Children with CF had higher liver fat than healthy children and depleted calf muscle choline at baseline. Muscle choline concentration increased in LXS and was associated with improvement in plasma choline status. No relevant changes in safety measures were evident. Conclusions: LXS had improved choline intake, plasma choline status, and muscle choline stores compared with placebo group. The choline-rich supplement was safe, accepted by participants, and improved choline status in children with CF.